2021
DOI: 10.1001/jamanetworkopen.2021.3040
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Care Handoffs Among Hospitalist Physicians and 30-Day Mortality in Hospitalized Medicare Beneficiaries

Abstract: Key Points Question What is the association between inpatient physician handoff and mortality among hospitalized Medicare patients? Findings In a national cross-sectional study of Medicare beneficiaries hospitalized with a general medical condition and treated by a hospitalist physician, physician handoff was not associated with increased mortality overall. In an exploratory analysis, among patients in the top quartile of estimated mortality, 30-day mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…A 2021 cross-sectional study evaluated the impact of physician hand-off among Medicare patients admitted to hospital in the US. 5 The authors restricted their analysis to hospitalists who worked at least 7 consecutive days and compared 30-day postdischarge mortality of patients with different probabilities of hand-off based on date of patient admission relative to handover schedule. Similar to our study, they found no overall association between physician hand-offs and 30-day mortality, although an exploratory analysis suggested an increase in 30-day mortality for patients with more severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 cross-sectional study evaluated the impact of physician hand-off among Medicare patients admitted to hospital in the US. 5 The authors restricted their analysis to hospitalists who worked at least 7 consecutive days and compared 30-day postdischarge mortality of patients with different probabilities of hand-off based on date of patient admission relative to handover schedule. Similar to our study, they found no overall association between physician hand-offs and 30-day mortality, although an exploratory analysis suggested an increase in 30-day mortality for patients with more severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…Further, hospitalists are generalists and may have discontinuous schedules. While these aspects of their job structure may provide benefits, such as reduced complications, LOS, and readmissions, they may also serve to fragment care or introduce more complexity for patients seeking answers to subspecialty specific questions, which could result in lower scores related to perceptions of communication and responsiveness in the Patient Experience domain 33–35 . These aspects of their work structure may further contribute to worse Patient Experience of care scores.…”
Section: Discussionmentioning
confidence: 99%
“…While these aspects of their job structure may provide benefits, such as reduced complications, LOS, and readmissions, they may also serve to fragment care or introduce more complexity for patients seeking answers to subspecialty specific questions, which could result in lower scores related to perceptions of communication and responsiveness in the Patient Experience domain. [33][34][35] These aspects of their work structure may further contribute to worse Patient Experience of care scores. The current work supports that idea as while there is a positive association between an increased hospitalist ratio and the Patient Experience domain, the 95% CI is relatively broad (0.20-4.77) and demonstrates a significance level of only less than .05.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be that efforts to improve the handoff of patients between physician shifts have led to a better quality of care by physicians taking care of patients over the weekend and, thus, fewer preventable adverse events. However, a recent study published in 2021 by Farid et al [ 26 ] showed that physician handoff was only associated with slightly greater mortality among patients with high illness severity. Nonetheless, there is a paucity of contemporary data regarding physician handoff and preventable adverse events.…”
Section: Discussionmentioning
confidence: 99%